Relationship between sustainable development and financial development from the perspective of the European green economy. Fuzzy approach - Zioło, Magdalena; Bąk, Iwona; Spoz, Anna; Oesterreich, Maciej; Niedzielski, Piotr; Raczkowski, Konrad (Frontiers in Environmental Science, 2023)
Introduction: Although a large number of publications are devoted to analyzing the relationship between financial development and economic growth, we focused on the answer to the question that sustainable development is accompanied by financial development in particular European Union countries. To our best knowledge, it is a new and original research approach that addresses important research gaps. Methodology: A synthetic indicator based on 13 variables was built to assess the level of sustainable development, taking into account the financial aspect. Fuzzy logic was used to assess the relationship between the level of sustainable development and financial development. It is an original and novel approach. Results: The research results showed significant differences between the north and south and Europe’s east and west. The highest levels of the synthetic measure for all analyzed periods were recorded for Sweden, Finland, and Denmark, and the lowest for Lithuania (2013), Cyprus (2014–2015), and Bulgaria (2016–2021). Over the nine years covered by the analysis, the level of sustainable development, considering the financial aspect, improved in two countries: Germany and Portugal, but deteriorated in six: Bulgaria, Croatia, Italy, Latvia, Romania, and Slovenia. In all analyzed years, the higher the level of the synthetic measure (sustainable development), the higher the value of the financial development index (FDI index). Discussion: When developing sustainable development policies, policymakers should consider their links with financial development and the policy of developing and regulating financial markets. Financial markets are essential for sustainability, and finance is a crucial driver of sustainable development.